PENGARUH INOVASI DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN TELKOMSEL DI KOTA BENGKULU - Ristiyanto, M. Ristiyanto; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research is motivated by the imperative for Telkomsel to continually enchance its innovation and product quality to sustain customer loyalty. The objective of this study is to ascertain the impact the innovation (X1) and product quality (X2) on customer loyalty (Y) among Telkomsel customers in Bengkulu City. The research question addressed is whether innovation and product quality significantly influence customer loyalty among Telkomsel usen in Bengkulu City. The research adopts a quantitative approach, focusing on Telkomsel customers in Bengkulu City as the study population. Based on the findings from the investigation into the influence of innovation and product quality on Telkomsel customers in Bengkulu City, it can be concluded that innovation significantly affects customer loyalty on Telkomsel customers in Bengkulu City, and product quality also has a significant impact on Telkomsel customer loyalty in Bengkulu City. Futhermore, innovation (X1) and product quality (X2) together exert a significant influence on customer loyalty (Y) among Telkomsel customers in Bengkulu City. The Coefficient of Determination Test (R2) yielded a value of 0.303, signifying that innovation (X1) and product quality (X2) contribute an influential proportion of 0.303 or 30.3% to customer loyalty (Y) among Telkomsel customers in Bengkulu City. The remaining 0.697 or 69.7% is influenced by other variables not considered in this study. Keywords: Innovation, Product Quality, Customer Loyalty